The essence of true HOMELAND. The ways of understanding the value of the HOMELAND by young Poles from Poland and Ukraine having Polish citizenship or formal adherence to the Polish nation = Istota prawdziwej OJCZYZNY. Sposoby rozumienia wartości OJCZYZNA przez młodych Polaków z Polski i Ukrainy posiadających polskie obywatelstwo lub formalną przynależność do narodu polskiego - Hopej, Malwina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article shows the conceptualization of concept Homeland - results of the survey conducted on a group of young Poles living in Lvov, Mościska (Mostyska), Wrocław and Legnica. The aim of this research is comparison of the understanding of Homeland by Poles living in different countries. The article consists of two parts: the first presents a description of the research method used by a team of linguists working under Prof. Jerzy Bartmiński`s leadership, which I used working on the second part, compiling the respondents` answers.
Keywords: homeland; Poland; Ukraine; polish minority; ojczyzna; Polska; Ukraina; mniejszość polska